Morphological characters of Species Members of the Solanaceae Family in Menoreh Samigaluh Hill, Yogyakarta - Luthfika, Muhammad; Martiwi, Ika Nugraheni Ari (Jurnal Biologi Tropis, 2024)
The Solanaceae family has 1,300 genera distributed in the sub-tropics and tropics. In Indonesia, the genus of the Solanaceae family is used as a source of food and medicine. Solanaceae as plants used for food, medicine and health care, require a precise and accurate identification process. Automatic plant identification can use visual morphological characteristics. Environmental conditions such as extreme temperatures, drought, and water stress cause plants to adapt. The adaptation process can induce morphological changes, this study aims to study the morphological characters of solanaceae in the karst area, the hills of the menorah samigaluh Yogyakarta. The data collection method uses Visual Encounter Census (VES) by purposive sampling. Data analysis was carried out in a qualitative descriptive manner. The results obtained three genera, and 7 species (Solanum melongena, Solanum torvum, Solanum lycopersicum, Solanum diphyllum, Capsicum annuum, Capsicum frutescens, and Physalis angulata). There are 23 morphological characters used as a reference in identifying species of Solanaceae members.